Assessing Stress Resilience After Smolt Transportation by Waterborne Cortisol and Feeding Behavior in a Commercial Atlantic Salmon (Salmo salar) Grow-Out Recirculating Aquaculture System - Höglund, Erik; Fernandes, Paulo; Rojas-Tirado, Paula; Rundberget, Jan Thomas; Hess-Erga, Ole-Kristian (Frontiers in Physiology, 2022)
Sampling protocols and water quality sensors have been developed to asses fish health and welfare in recirculating aquaculture systems (RAS). Still, the use of fish-based non-invasive welfare indicators, reflecting the physiological state of the fish, is limited in this type of system. Cortisol, the major stress coping hormone in fish, diffuses through the gills. Consequently, waterborne cortisol is a potential fish- based non-invasive welfare indicator in RAS. However, it’s use in commercial rearing systems is spares. In this study we evaluated water cortisol levels and feeding behavior as welfare indicators of newly inserted smolt in a commercial RAS for harvest size Atlantic salmon. The RAS consisted of two parallel fish rearing raceways, raceway 1 and 2, sharing the same water treatment with common outlets and inlets. The smolts were inserted in raceway 1 while salmon that have been in the system for six month or more were kept in raceway 2. The smolt insertion period was three days. Samples for water cortisol levels were withdrawn the day before, one and three days after smolt insertion period. Smolt insertion resulted in elevated water cortisol concentrations in the entire system, with the highest values in raceway one the day after smolt insertion. Estimated cortisol production in newly inserted smolt decreased over time was similar to what has been reported in salmon adapting to experimental tanks. Feeding behavior indicated that the appetite was not fully resumed in the newly inserted smolts, while the appetite of fish in raceway 2 was unaffected by smolt insertion. These results, obtained in a highly intensive commercial RAS, suggests that waterborne cortisol together with feeding behavior can be used as indicators for adaptive processes associated with stress resilience in farmed fish. Thus, they are promising non-invasive indicators for assessing the impact of potential stressors on fish welfare in this type of rearing system